2012
DOI: 10.1007/s00330-012-2656-2
|View full text |Cite
|
Sign up to set email alerts
|

Image quality of ultra-low radiation exposure coronary CT angiography with an effective dose <0.1 mSv using high-pitch spiral acquisition and raw data-based iterative reconstruction

Abstract: Coronary CT angiography with an estimated effective dose <0.1 mSv may provide sufficient image quality in selected patients through the combination of high-pitch spiral acquisition and raw data-based iterative reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 30 publications
2
90
1
Order By: Relevance
“…While SNR and CNR improved in SAFIRE images of patients weighing 75 kg and below, no improvements were noted in patients that were heavier than 75 kg, in a study which evaluated the performance of SAFIRE in coronary CT angiography. 45 The results are in line with a separate study by Wang et al 46 on obese patients with a body mass index (BMI) larger than 30 kg/m 2 . Another study investigating the use of SAFIRE in cervical spine CT examinations meanwhile noted that while increasing the iteration strength level of the SAFIRE algorithm improved visualization of the intervertebral discs and ligaments, the use of a higherstrength SAFIRE algorithm resulted in poorer visualization of soft tissues and trabecular bone.…”
Section: Performance Of Safire and Admire Algorithmssupporting
confidence: 87%
“…While SNR and CNR improved in SAFIRE images of patients weighing 75 kg and below, no improvements were noted in patients that were heavier than 75 kg, in a study which evaluated the performance of SAFIRE in coronary CT angiography. 45 The results are in line with a separate study by Wang et al 46 on obese patients with a body mass index (BMI) larger than 30 kg/m 2 . Another study investigating the use of SAFIRE in cervical spine CT examinations meanwhile noted that while increasing the iteration strength level of the SAFIRE algorithm improved visualization of the intervertebral discs and ligaments, the use of a higherstrength SAFIRE algorithm resulted in poorer visualization of soft tissues and trabecular bone.…”
Section: Performance Of Safire and Admire Algorithmssupporting
confidence: 87%
“…An alternative approach for obtaining single heart beat coverage is by using fast table movement (high-pitch) spiral acquisition protocols, currently only possible with DSCT systems. 34 …”
Section: Patient Selection and Preparationmentioning
confidence: 99%
“…7,25,26 Schuhbaeck et al demonstrated that for a coronary-CT, the addition of high-pitch with raw databased iterative reconstruction results in a furthermore decrease in dose, while providing sufficient image quality with an estimated effective dose <0.1 mSv. 27 In the present study, the acquisition protocol was optimized for CTA of the thoraco-abdominal aorta and not exclusively for the heart. Yet the effective dose was a mean of 3.9 ± 1.5 mSv.…”
Section: Discussionmentioning
confidence: 99%